Light perception in two mole-rat species, the silvery mole-rat (Heliophobius argenteocinereus) and the giant mole-rat (Fukomys mechowii). - Kott, Ondřej (Jihočeská univerzita, 2008)
Sight in subterranean mammals living in a dark ecotope has generally been assumed as not needed and therefore greatly diminished in its function. Recent neuroanatomical studies demonstrate unexpected preservation of the visual system of several African mole-rats (Bathyergidae, Rodentia). Only a few behavioural studies, testing visual abilities and discussing their adaptive significance in these rodents, have been published to date. A spontaneous preference to light stimuli of two mole-rat species, the silvery mole-rat (Heliophobius argenteocinereus) and the giant mole-rat (Fukomys mechowii), was tested in this study. Assessed results showed convincingly that both species are able to perceive light. The following experiments provided the first behavioural support to the perception of short-wavelengths in this intensively studied group of subterranean rodents.
Light perception in two mole-rat species, the silvery mole-rat (Heliophobius argenteocinereus) and the giant mole-rat (Fukomys mechowii).
Keywords: African mole-rats; sight; subterranean mammals; light perception; photoreceptors; retina